Reprogramming of Embryonic Human Fibroblasts into Fetal Hematopoietic Progenitors by Fusion with Human Fetal Liver CD34(+) Cells - Sandler, Vladislav M. (Public Library of Science, 2011)
Experiments with somatic cell nuclear transfer, inter-cellular hybrid formation_ENREF_3, and ectopic expression of transcription factors have clearly demonstrated that cell fate can be dramatically altered by changing the epigenetic state of cell nuclei. Here we demonstrate, using chemical fusion, direct reprogramming of the genome of human embryonic fibroblasts (HEF) into the state of human fetal liver hFL CD34+ (hFL) hematopoietic progenitors capable of proliferating and differentiating into multiple hematopoietic lineages. We show that hybrid cells retain their ploidy and can differentiate into several hematopoietic lineages. Hybrid cells follow transcription program of differentiating hFL cells as shown by genome-wide transcription profiling. Using whole-genome single nucleotide polymorphism (SNP) profiling of both donor genomes we demonstrate reprogramming of HEF genome into the state of hFL hematopoietic progenitors. Our results prove that it is possible to convert the fetal somatic cell genome into the state of fetal hematopoietic progenitors by fusion. This suggests a possibility of direct reprogramming of human somatic cells into tissue specific progenitors/stem cells without going all the way back to the embryonic state. Direct reprogramming of terminally differentiated cells into the tissue specific progenitors will likely prove useful for the development of novel cell therapies.